Prevalence and Clinical Characteristics of Aquagenic Pruritus among Medical and Pharmacy Students in Lomé (Togo) - Julienne Noude Teclessou; Koussake Kombate; Abla Sefako Akakpo; Abas Mouhari-Toure; Julie Zoua; Panawe Kassang; Bayaki Saka; Palokinam Pitche (Hindawi Limited, 2020)
Objective. The aim of this study was to determine the prevalence and clinical characteristics of aquagenic pruritus (AP) in medical students in Lomé (Togo). Methods. This was a prospective and descriptive study conducted among medical students in Lomé from June 1st to August 30th, 2019. The data collection questionnaire was anonymous composed of sociodemographic variables, bathing habits, and history of allergy responding to the concept of aquagenic pruritus and its characteristics. Results. In our study, 129/591 medical students had AP, giving a prevalence of AP to 21.8%. The average age of students with AP was 23.9 years, and the M/F sex ratio was 1.5. AP was not present after each bath in 100% of the medical students who suffered from it and lasted an average of 9.09 minutes. It was characteristically pruritic (60.5%) or tingling (38.0%) and localized (45.0%) or generalized (55.0%) in respondents with history of AP. There was a significant association between the presence of AP and a personal history of allergic rhinitis (p<0.01) and the presence of AP and a family AP (p<0.01). Twenty-six (20.2%) respondents with AP feared taking a bath. Bathing with warm or lukewarm water (29.5%) or applying menthol ointment (27.1%) were the main precautions taken to reduce AP. Conclusion. Aquagenic pruritus is a common condition in medical students in Togo. It occurs mainly in males and can be familial.